Impaired player-coach perceptions of exertion and recovery during match congestion - Doeven, S. H.; Brink, M. S.; Frencken, W. G. P.; Lemmink, K. A. P. M. (International Journal of Sports Physiology and Performance, 2017)
During intensified phases of competition, attunement of exertion and recovery is crucial to maintain performance. Although a mismatch between coach and player perceptions of training load is demonstrated, it is unknown if these discrepancies also exist for match exertion and recovery.